2005
DOI: 10.1507/endocrj.52.743
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Gastric Carcinoid Causing Ectopic ACTH Syndrome: Discrepancy of Plasma ACTH Levels Measured by Different Immunoradiometric Assays

Abstract: Abstract. Discrepancy of plasma ACTH levels measured by different immunoradiometric assays (IRMA) in a case with malignant gastric carcinoid causing ectopic ACTH syndrome was examined by gel chromatography and immunohistochemical analysis. A 49-year-old male was found to have a large gastric tumor, with muscle wasting, hypertension, diabetes and hypokalemia caused by hypercortisolemia. His plasma ACTH levels, although initially elevated, were found to be almost in normal ranges. The discrepancy of plasma ACTH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Diagnostic imaging test by SRS not available in Japan yet was approved by the Ethics Committee of TMDU Hospital; written informed consent was obtained from each patient. Some cases have been reported elsewhere [5][6][7][8][9][10].…”
Section: Patientsmentioning
confidence: 98%
See 1 more Smart Citation
“…Diagnostic imaging test by SRS not available in Japan yet was approved by the Ethics Committee of TMDU Hospital; written informed consent was obtained from each patient. Some cases have been reported elsewhere [5][6][7][8][9][10].…”
Section: Patientsmentioning
confidence: 98%
“…A confirmed diagnosis of EAS (proven EAS) was made in 10 cases by demonstration of the presence of tumor debulking of advanced neuroendocrine carcinoma with multiple liver metastases, originated from the stomach (Case 5) [6], and the pancreas (Case 6) [7]. Multidisciplinary therapy, including transhepatic arterial embolization, systemic chemotherapy (adriamaycin, dacarbadine, streptozotocin, and fluorouracil), α-interferon, and finally liver transplantation was performed in Case 6 [7].…”
Section: Diagnostic Imaging Testsmentioning
confidence: 99%
“…Furthermore, it was reported that expression of PC1/3 was investigated in various endocrine tumors [15]. in contrast, it was indicated that aberrant processing of PoMC might be observed in ectopic aCTH producing tumors [16]. immunohistochemical analysis in this study revealed that immunostaining for PoMC, PC1/3, and aCTH were positive in the tumor cells.…”
Section: Discussionmentioning
confidence: 52%
“…Resected tumor tissues were subjected to immunohistochemical studies for ACTH by Envision method (DAKO: Carpinteria, CA) using anti-ACTH monoclonal antibody (1 : 200; DAKO) which could not recognize POMC [9], and PC1/3 by avidin-biotin peroxidase complex method using anti-PC1/3 polyclonal antibody (1 : 400; Chemicon Int,. CA) as previously reported [9].…”
Section: Immunohistochemistrymentioning
confidence: 99%